STRATEGI INTERVENSI KESEHATAN LANSIA DI POSYANDU - Yoktan Samb Metkono (Jurnal Ilmu Kesehatan Masyarakat, 2017)
The number of elderly in Indonesia keeps increasing from 7.69% in 2011 be 8.1% in 2013. With the increasing number of elderly than so much heath problems that happened in elderly. The efforts are being mad by the government to cope the problems in elderly is holding Posyandu of elderly. The Posyandu of elderly is Integrated Service pos held to elderly so their can monitor the condition his health every month. to describe intervention strategies healthy of elderly to increases their status in Posyandu in the Puskesmas Getasan. The research is qualitative descriptive. The data collected use in depth interview by interview guidelines. The research done in the area of PuskesmasGetasan , Semarang, Central Java. In January to March 2017. The participants numbered 8 people obtained by using purposive sampling techniques. The research use data analysis from Miles and Humberman. Posyandu elderly held every month through five tables of activities that is driven by health workforce from Puskesmas and cadre in tre select from community. However there are still barriers is lock of awareness from elderly to make a visit so extension done by health workforce to elderly and their family through organization’s in community. The evaluation to monitor the visit and health condition from elderly done once a month. Conclusion: Posyandu elderly who in invented already well underway because already participating from health workforce and community is good. Howeverhealth workforce should be more plays again, so can increase knowledge from elderly about Posyandu benefits so the visit from elderly more on the rise. Keyword keys : Strategies, Elderly, Posyandu.